Peningkatan literasi bahaya narkoba pada siswa SMP Negeri 5 Kandis dan SMA Negeri 2 Kandis - Razkia, Dwita; Juliharsyah, Arya Dwi; Wardani, Kurnia Vera; Pratiwi, Tri Rahayu; Yusnira, Dina; Rivaldo, Leoky; Cahyaningrum, Eunike Danis; Azani, M Teja; Dewi, Ratna Sari; Saragih, Rendra Deardo; Pratama, Arya Sapta; Rahmawati, Aci; Chantika, Bunga; Darini, Darini (Nur Science Institute, 2025)
Drug abuse poses a serious threat to Indonesia's young generation, particularly among junior and senior high school students who are highly vulnerable to peer influence. As a form of community service, the Community Service Program (KKN) team conducted a drug abuse awareness campaign at SMPN 5 Kandis (400 students) and SMAN 2 Kandis (500 students) on September 3, 2025. The activity involved 13 students from the Belutu Village KKN group in collaboration with village officials, healthcare workers, and school representatives. The implementation methods included a pre-test, interactive lectures, group discussions, Q&A sessions, and a post-test to measure improvement in students' understanding. The results showed a significant increase in the